Daya Terima Dan Kadar Zat Besi (Fe) Serundeng Ampas Kelapa - Yuda Astina, Kadek; Gede Dharmawan, I Bagus; Bagus Pudja Erdika, I Putu (Journals of Ners Community, 2023)
Knee Coil is a volume coil that can act as a transmitter and receiver at the same RF signal. Flex Coil is a surface coil which has a high SNR for a superficial examination (a small organ). The purpose of this research is to know comparison the value of signal to noise ratio (SNR) and higher the value of signal to noise ratio (SNR) at MRI Wrist Joint examination using Knee Coil and Flex Coil. Type of this research is quantitative experimental approach. The research data which 10 samples. Assessments are performed on the whole Wrist Joint and per anatomic criteria subjectively Carpometacarpal Joint, Midcarpal Joint, Radiocarpal Joint, Schapoid, Lunatum dan Triquetrum. Then the results of the data in Paired T-Test tested. Test results that there are differences in comparison the value of signal to noise ratio (SNR) at MRI Wrist Joint examination using Knee Coil and Flex Coil which has a smaller Ï Value (<0,05) per anatomic criteria and whole Wrist Joint. This is consistent with the results of the calculation of the average SNR value on the higher Knee Coil that is 143.84 because the coil acts as transreceiver and has two preamplifiers so as to improve the SNR. Conclusion: There is a difference in comparison the value of Signal To Noise Ratio (SNR) at MRI Wrist Joint examination using Knee Coil and Flex Coil.